2008
DOI: 10.4137/cmo.s627
|View full text |Cite
|
Sign up to set email alerts
|

Primary Adrenal Leiomyosarcoma: A Case Report and Literature Review

Abstract: Summary:The case presented here illustrates a 75 year old female patient who underwent surgical resection of a right adrenal mass of uncertain nature. The fi nal histological diagnosis was consistent with leiomyosarcoma arising from the adrenal anatomic site. Primary leiomyosarcoma of the adrenal gland is a very rare malignant mesenchymal neoplasm: to our knowledge, this is only the twelfth case reported in literature. We describe the clinical course and a brief review of clinical and histological features, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 19 publications
0
26
0
2
Order By: Relevance
“…Twenty cases have been reported in the English literature since 1981. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Typically, the disease presents as a symptomatic retroperitoneal mass more than 10 cm in diameter. It can be associated with a mass effect on surrounding organs, involvement of the inferior vena cava (IVC) by a tumor thrombus, local organ invasion or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty cases have been reported in the English literature since 1981. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Typically, the disease presents as a symptomatic retroperitoneal mass more than 10 cm in diameter. It can be associated with a mass effect on surrounding organs, involvement of the inferior vena cava (IVC) by a tumor thrombus, local organ invasion or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…[3] A review of the literature revealed only twelve previously reported cases of PAL. [2] The reported age of patients ranged from 30 to 75 years with approximately equal frequency in males and females. All these tumors ranged in size from 11 to 25 cm in greatest dimension.…”
Section: Discussionmentioning
confidence: 98%
“…[1] Reviewing the literature, we encountered only twelve previously reported cases of primary adrenal leiomyosarcoma (PAL). [2] We believe that this is the thirteenth case of PAL. It has a wide range of differential diagnosis including MPNST, malignant melanoma, gastrointestinal stromal tumour (GIST); metastatic carcinoma and others.…”
Section: Introductionmentioning
confidence: 93%
“…Radical surgical resection of the tumor is the main goal of therapy. Some authors advocate postsurgical adjuvant radiation therapy for locally advanced malignant disease (10,11). In a recent report, Murart et al (14) suggested that radical surgical resection without adjuvant therapies might be an alternative approach for low-grade leiomyosarcomas.…”
Section: Discussionmentioning
confidence: 99%